PENGARUH PENGGUNAAN MEDIA VIDEO DALAM PENYULUHAN KESEHATAN GIZI TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA - Septiani, Dini Tri; Ginting, Ade Krisna (JURNAL KESEHATAN INDRA HUSADA, 2024)
Based on 2018 basic health research data, it was found that there was an increase in the prevalence of anemia at the age of 15-24 years, namely 32% or 14.7 million people, which means 3 out of 10 children experience anemia. The aim of this research is to determine the effect of using video media in nutritional health education on adolescent girls' knowledge about anemia at SMAN 1 Pebayuran. This research uses an experimental method using quasi-experimental techniques, a one group pre and posttest design approach. The population of this study were all female teenagers from SMAN 1 Pebayuran class X aged 15-17 years. The sampling technique was proportional random sampling, the number of samples was 30 students. Research data was collected using a questionnaire. The research results obtained were that before being given counseling using videos, the majority of young women's knowledge level had a mean value of 54.14 and after providing counseling using videos, the majority of young women's knowledge levels increased with a mean value of 93.31. The results of the T-test obtained a p value of 0.000 < α 0.05, which means that there is an influence of the use of video media in nutritional health education on the knowledge of young women. The conclusion of this study was that it was proven to significantly increase adolescent girls' knowledge about anemia after being given counseling using videos. Therefore, health workers are expected to see the opportunity to use educational videos as an appropriate alternative media in providing health and nutrition education as an effort to increase teenagers' knowledge about anemia